High Neutrophils to Lymphocytes Ratio in Maternal Blood Serum as Risk Factor for Preterm Premature Rupture of Membrane - Nicholas Renata Lazarosony; I Wayan Artana Putra; Ryan Saktika Mulyana; I Made Darmayasa; Ida Bagus Gde Fajar Manuaba; I Gde Sastra Winata; I Nyoman Gede Budiana (International Journal of Social Service and Research, 2023)
Introduction: Neutrophil-to-lymphocyte ratio (NLR) has been extensively studied as a prognostic factor for various diseases based on systemic inflammation. Premature rupture of membranes (PROM) is an obstetric problem that does not only occur in term pregnancies but can also occur in preterm pregnancies. One of the main etiologies for premature rupture of membranes is inflammation. Knowing the difference in the NLR between preterm prematurerupture of membranes (PPROM) and without PPROM is important to increase understanding of the crucial role of NLR in predicting the incidence of PPROM. Method: This analytic case-control study compared NLR values ??in maternal blood serum between PPROM and without PPROM. This research was conducted in the emergencydelivery room and obstetrics and gynecology outpatient clinic at Prof. dr. I.G.N.G. Ngoerah Hospital Denpasar from February to June 2022. Results: A high NLR in maternal blood serum may be a risk factor for PPROM. Patients with a high NLR had a 4.5 times greater likelihood of experiencing PPROM than those with a low NLR (OR = 4.5; 95% CI = 1.4 – 13.83; p = 0.007). Conclusion: A high NLR in maternal blood serum is a marker of inflammation with an increased risk of 4.5 times for the occurrence of PPROM.